Efficacy of an Enteral Feeding Protocol for Providing Nutritional Support after Paediatric Cardiac Surgery. Issue 5 (September 2015) - Yoshimura, S.; Miyazu, M.; Yoshizawa, S.; So, M.; Kusama, N.; Hirate, H.; Sobue, K.
Enteral nutrition (EN) is considered to be a more appropriate method than parenteral feeding for providing nutrition to critically ill children. However, children who undergo cardiac surgery are at high risk of postoperative gastrointestinal complications during EN. The purpose of this study was to demonstrate the safety and efficacy of our EN feeding protocol after paediatric cardiac surgery through comparison between a single-centre prospective case series and historical cases. Forty-seven children who were admitted to the ICU after cardiac surgery were enrolled ('post group'). Data for these children were compared with a similar cohort of children who were admitted before the implementation of the feeding protocol (n=62; 'pre group'). The incidence of complications including vomiting, necrotising enterocolitis and hypoglycaemia; the time until the initiation of EN; and the changes in calories provided were compared between the groups. The frequency of vomiting was significantly lower in the post group than in the pre group (36.2% versus 58.0%, P =0.038), and necrotising enterocolitis did not occur in either group. The time until the initiation of EN and the total calories provided did not differ significantly; however, in the post group the proportion of energy provided by parenteral nutrition was significantly smaller ( P <0.001), and provided by EN was significantly larger ( P =0.003), than in the pre group. The frequency of hypoglycaemia was similar in both groups. This study showed that our EN protocol resulted in adjustments to calories provided via EN versus parenteral nutrition after paediatric cardiac surgery, and reduced the frequency of vomiting.